Gender and Age Differences in Short- and Long-Term Outcomes Following Primary Percutaneous Coronary Intervention for ST-Elevation Myocardial Infarction - Chua, Su-Kiat (Zhonghua Minguo Xin Zang Xue Hui Za Zhi, 2014)
BACKGROUND: Studies have reported that women with ST elevation myocardial infarction (STEMI) have worse short- and long-term outcomes than men. It has not yet been confirmed whether these differences reflect differences in age between men and women. METHODS: We retrospectively enrolled 1035 consecutive STEMI patients treated with primary percutaneous coronary intervention (PCI). Baseline clinical characteristics, coronary anatomy, and outcome were compared between young (< 65 years old) and older patients (≥ 65 years old) of both sexes. RESULTS: Younger women presented with a lower incidence of typical angina (83% vs. 93%, p = 0.03), single-vessel disease (21% vs. 35%, p = 0.03), and total occlusion of infarct-related artery (65% vs. 83%, p = 0.001) than younger men, with no gender difference noted in the older group. Younger women in the study had a higher incidence of reinfarction, heart failure requiring admission, or mortality (23% vs. 6%, p < 0.001) during follow-up, compared with younger men, with no gender difference in the older group. Using the Kaplan-Meier analysis, younger women had lower rates of event-free survival (p < 0.001 by log-rank test) than younger men, with no gender difference in the older group. In multivariate analysis, age could predict long-term outcome in men (Hazard ratio 4.43, 95% confidence interval: 2.89-6.78, p < 0.001) but not in women. CONCLUSIONS: In STEMI patients receiving primary PCI, sex-related long-term outcome differences were age-dependent, with younger women likely to have a worse long-term outcome when compared with younger men.